POSITIVE LEGISLATURE MAHKAMAH KONSTITUSI DI INDONESIA (IAIN Tulungagung, 2017)
In a judicial review, Constitutional Court normatively perform merely only as a negative legislator which is only to invalidate or abolish the norms. Nowadays, the facts show that Constitutional Court in some cases not only invalidate the norm, but also has made verdicts that is forming a law. This study aimed, to identify and analyze more deeply whether the Constitutional Court has made a positive function of legislature through its decisions. To analyze the various legal implications arising from the decision of the Constitutional Court which makes the new norm, and how to realize it. This is normative research with case approach, the conceptual approach and the statute approach. Decisions that can be categorized as positive legislature are Decision No. 46 / PUU-VIII / 2010, No. 102 / PUU-VII / 2009, and No. 110-111-112-113 / PUU-VII /2009. Those Constitutional Court verdicts that contain positive legislature are considered as a part of progressive law enforcement. Those verdicts were made based on legal, philosophical, and sociological consideration which can not be separated from law interpretation. Law can not be seen only from its textual view, but we also have to live up the benefits from its contextual view.Keywords: Constitutional Court, Negative Legislator,Positive Legislator